IMPROVEMENT OF PTCA GUIDE WIRE PRODUCTION BY DESIGN OF EXPERIMENT - Leenatham, Athiwat (Srinakharinwirot University Engineering Journal, 2019)
The purpose of this research was to reduce defects from grinding process of PTCA Guide Wire production. All of defects in Grinding process were from various problem, the main problem was diameter after grinding was not standardized 0.061 mm specified by QC department. The controllable variables of grinding machine are pressure, angle and sand paper, the response factor is diameter is in standard. 2k Factorial was practice in this research with 5 replicates. The result of ANOVA shows that factor affecting on diameter are all of main factors and interaction factors. To identify the optimize factors, the researcher use regression model and Optimization response function in MINITAB, result shows that pressure 6.50 angle 10.0667 and Extra-fine are factors that effect to diameter within acceptable range. Twenty additional samples of PTCA guide wire were collected after all factors were established then tested by using T-test, the hypothesis is samples are equal to 0.061 or not. The result shows that these samples are equal to 0.061 at 0.05 significant level. All Factors are implemented to currently production, the defect was collect from the same initial period of this research. The result shows that the defect before and after are 108 and 13 or reducing 87.96% respectively.